Answer:
R = sqrt[(IWL)^2/(E^2 - I^2)] or R = -sqrt[(IWL)^2/(E^2 - I^2)]
Step-by-step explanation:
Squaring both sides of equation:
I^2 = (ER)^2/(R^2 + (WL)^2)
<=>(ER)^2 = (I^2)*(R^2 + (WL)^2)
<=>(ER)^2 - (IR)^2 = (IWL)^2
<=> R^2(E^2 - I^2) = (IWL)^2
<=> R^2 = (IWL)^2/(E^2 - I^2)
<=> R = sqrt[(IWL)^2/(E^2 - I^2)] or R = -sqrt[(IWL)^2/(E^2 - I^2)]
Hope this helps!
To find f(-20), first figure out which piece x = -20 fits with.
Since -20 < -12, x = -20 first in the domain used by the third piece.
For f(-20), treat this function as if it was just f(x) = 3x-7.
f(-20) = 3(-20) -7
= -60 - 7
= -67
Answer:
![\text{D. 36.64}](https://tex.z-dn.net/?f=%5Ctext%7BD.%2036.64%7D)
Step-by-step explanation:
The Law of Sines is given by
and works for any triangle.
Therefore, we have the proportion:
![\frac{c}{\sin 41.5^{\circ}}=\frac{37}{\sin 42^{\circ}},\\\\c=\frac{37\sin 41.5^{\circ}}{\sin 42^{\circ}}=36.6399945706\approx \boxed{36.64}](https://tex.z-dn.net/?f=%5Cfrac%7Bc%7D%7B%5Csin%2041.5%5E%7B%5Ccirc%7D%7D%3D%5Cfrac%7B37%7D%7B%5Csin%2042%5E%7B%5Ccirc%7D%7D%2C%5C%5C%5C%5Cc%3D%5Cfrac%7B37%5Csin%2041.5%5E%7B%5Ccirc%7D%7D%7B%5Csin%2042%5E%7B%5Ccirc%7D%7D%3D36.6399945706%5Capprox%20%5Cboxed%7B36.64%7D)